The action taken in the process of social rehabilitation of socially maladjusted girls: their parents' perspective - Justyna Maria Siemionow (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
This is a report on the research which was undertaken in a corrective institution for socially maladjusted girls. A total of 45 parents of socially maladjusted girls took part in this study. The main research problem was the question: What kind of changes in the socially maladjusted girls' behavior are their parents able to recognize? The starting point is one thesis: the cooperation with the family is essential to change the pupils behavior. Very often family is considered to be the basic and the most primary educational environment due to its significant impact on the development of a child. At times, parents cannot fulfill their fundamental duties and the child is sent to the Juvenile Education Centre by Court. The family is considered as an active participant in the process of social rehabilitation. This process is effective when all its participants cooperate to meet individual and collective needs. The institution tries to create the strong bonds between all the participants of social rehabilitation process: juveniles, their parents and the staff. The parents feel the effects of the social rehabilitation process influence the child. It is extremely important for them to discuss about that matter with the teachers and instructors working in the centre. The process of exchanging information and reacting to changes is very important and essential. This article includes the proposal of research which can be done by any institution to increase the level of effectiveness.